Analysis of Adolescent Reproductive Health Preventive Effort in Reproduction Material on Junior High School Science Book - Elsa Yuniarti; Muhyiatul Fadilah; Rahmawati Darussyamsu; Nur Azmi (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2017)
Adolescent knowledge about reproductive health is still low, it causes high cases of adolescent reproductive health. Lack of adolescent knowledge about reproductive health is caused by several factors such as lack of information about reproductive health among adolescents. One way to increase adolescent knowledge is to provide knowledge about true reproductive health through the education process. In formal education about reproductive health has been published as part of the curriculum and described in KD 4.1. It presents the results of tracing information from various sources related to health and prevention efforts for reproductive organ disorders. The purpose of this study is to determine the percentage of adolescent reproductive health preventive efforts in the reproduction system materials in the integrated science books SMP. This research is descriptive research. Population and sample in this research is material of reproduction system which is found in integrated science book of junior high school which is mostly used by junior high school student in Padang city, that is book of Kemendikbud, Erlangga, and Yudhistira. Samples were taken by purposive sampling technique. Data collection uses book analysis instruments that contain indicators of adolescent reproductive health preventive efforts. Data analysis techniques are performed using percentages for each category and determine the coefficient of agreement.The results showed that the percentage of adolescent reproductive health preventive efforts in books Kemendikbud 62%, Erlangga 39%, and Yudhistira 44%. So it can be concluded that the three books are still less presenting efforts to prevent adolescent reproductive health is <70%.